Conservation of Litsea Deccanensis: An NTFP under Local Extirpation - Mishra, C. K.; Ramakrishna Naidu, G. (Indian Forester, 2013)
Population of Litsea deccanensis is dwindling due to unscientific harvest and over exploitation. In the present paper matrix population model has been applied to study the behavior of NTFP, Litsea deccanensis, which is on decline in the Chittoor district of Andhra Pradesh due to over exploitation from bark extraction. Its conservation measures have been suggested.